Esophageal two-phase supine/standing scintigraphy and balloon dilatation in achalasia: 20 years of experience - Janković Zoran; Pucar Dragan; Doder Radoje; Perišić Nenad (Vojnosanitetski Pregled)
Background/Aim. The most frequent therapeutic method for achalasia is balloon dilatation (BD). Esophageal scintigraphy is potentially the most convenient method for the evaluation of achalasia by quantifying esophageal transit. The aim of this study was to present the results of esophageal scintigraphy (ES) in achalasia treated by BD for a long period of time, from 1997 to 2016, and to set parameters suitable for predicting treatment outcomes. Methods. Two-phase ES in anterior projection was performed. The first phase involved swallowing 10 mL of water with 18.5 MBq 99mTc in a supine position. The second phase was performed in a standing position after swallowing 100 mL of water. The retention index (RI) of esophageal radioactivity was calculated after the imaging using registered esophageal and gastric counts. ES was performed in 52 patients (34 males and 18 females, aged 22–75 years, the median age 44 years) before and after BD. In 31 patients, only two scintigraphies were performed. In the remaining 21 patients, follow-up and repeated scintigraphies were continued including the patients with therapeutic failure and repeated BD. BD was repeated in 8 patients, and those were followed up and evaluated over time. Modified BD was performed with Rigiflex balloon dilators. Results. A typical scintigraphic finding in the supine position was passive esophageal filling without the evidence of motility, and in most patients, 43 of them (83%), radionuclide elimination in the stomach was absent. Evaluating values before and long after the first BD, it was shown that certain values of RI indicated remission or relapse of the disease. The RI difference higher than 50% after BD was a reliable indicator of a longer remission. The age and gender of patients had no impact on the outcome of dilatation, but younger patients were with a higher risk of early failure (6 patients during the first year after BD). ES showed that the first BD was initially successful in 50 patients and after the follow-up in 41 (79%) patients. Conclusion. A two-phase supine/standing ES is most suitable for diagnosing and the follow-up of achalasia. RI represents an important parameter for the evaluation and prediction of therapeutic response. The RI difference of more than 50% after BD is a reliable predictor of a longer remission. Age and gender have no impact on dilatation outcome, but patients younger than 40 years have a higher risk of early therapeutic failure.